Molecular docking of phytosterols in Stenochlaena palustris as anti-breast cancer - Dona Marisa; Lisda Hayatie; Siti Juliati; Eko Suhartono; Noer Komari (Acta Biochimica Indonesiana, 2021)
Background: Stenochlaena palustris, also known as kelakai or lemidi, is frequently linked to anti-inflammatory, anti-bacterial, anti-fungal, and antioxidant properties. S. palustris phytosterols are suggested to suppress the progression of breast cancer. Objective: The objective of this study is to evaluate the potential of phytosterols found in S. palustris to act as estrogen receptor (ER) inhibitors. Methods: Phytosterols (alpha-tocopherol, beta-sitosterol, campesterol, stigmasterol, fucosterol) were docked to estrogen receptor (PDB ID: 7KBS). Molecular docking parameters included Gibb's free energy and interactions between ligand and protein. ADMET properties were analyzed using pkCSM and SwissADME. Results: Alpha-tocopherol showed the highest interaction with the estrogen receptor with ΔG value -8. 9254 kcal/mol (the native ligand, raloxifene, had a G value of -12.052 kcal/mol). Leu387 (hydrogen bond); Phe404 (Phi-phi-T shaped), Leu391, Leu346, Trp383, Leu354, Ala350, Leu525, Leu349 (Alkyl) were among the residues by which a-tocopherol interacted with ER. Alpha-tocopherol has no hepatotoxicity and no skin sensitization. Conclusion: By suppressing ERa, phytosterols from S. palustris may have potential anti-breast cancer activity and may be used to prevent estrogen-dependent human cancers like breast cancer.